Altered Levels of Mitochondrial DNA Are Associated With Female Age, Aneuploidy, and Provide an Independent Measure of Embryonic Implantation Potential. Issue 1 (January 2016) - Fragouli, Elpida; Spath, Katharina; Alfarawati, Samer; Kaper, Fiona; Craig, Andrew; Michel, Claude-Edouard; Kokocinski, Felix; Cohen, Jacques; Munne, Santiago; Wells, Dagan
Abstract : Obstet Gynecol Surv 2016;71(1):28–29 The early embryo has high-energy requirements as it divides and differentiates before implantation. The energy needed to support the initial stages of preimplantation development is supplied by mitochondria.